Additive Manufacturing of Sandwich–Structured Conductors for Applications in Flexible and Stretchable Electronics. Issue 9 (23rd July 2021) - Yu, Xiaowei; Gong, Xiangtao; Podder, Chinmoy; Ludwig, Brandon; Chen, I-Meng; Shou, Wan; Alvidrez, Alexis; Chen, Genda; Huang, Xian; Pan, Heng
Abstract : Additive manufacturing methods have shown great potentials to substitute the costly and time‐consuming conventional subtractive methods in the processing of electronically conductive materials for applications in flexible and stretchable electronics. Herein, additive manufacturing of highly conductive, sandwich‐structured conductors with high‐temperature processibility and versatility in applicable substrates is reported. The sandwich‐structured conductors with silver nanoparticles (Ag NPs) as electronic conductors and polyimide (PI) as encapsulation are layer‐by‐layer deposited by aerosol printing into PI/Ag/PI composites. A high annealing temperature of 250 °C contributes to the high electronic conductivity of the Ag layer at 1.14 × 10 7 S m −1, which is in the same order of magnitude to the conductivity of bulk Ag at 6.3 × 10 7 S m −1 . The high annealing temperature also significantly improves the interfacial bonding between the Ag and PI layers. For applications in flexible and stretchable electronics, the sandwich‐structured conductors are transferrable to various substrates through a thiol−epoxy bonding process, including polystyrene (PS), polyethylene terephthalate (PET), Kapton, and polydimethylsiloxane (PDMS) thin films. The sandwich‐structured conductors transferred to flexible and stretchable substrates exhibit highly retained electronic conductivity under deformations such as bending and stretching. Abstract : Additive manufacturing of PI/Ag/PI sandwich‐structured conductors with high‐temperature processibility and versatility in applicable substrates is reported. The high processing temperature contributes to high electronic conductivity of Ag layer and significant improvement in bonding of PI/Ag interface. The conductors are transferrable to various substrates including PS, PET, Kapton, and PDMS with highly retained electronic conductivity under bending and stretching deformations.